Utilization of Turmeric and Tamarind as Herbal Medicine Turmeric Tamarind in Sentul Village, Serang Regency - Afiah, Siti; Dzulfiani, Nayla Alifah; Maryati, Dea; Salsabilah, Risa; Komalasari, Nivia Ayu; Fitriana, Desi Eka Nur (Jurnal Biologi Tropis, 2025)
Turmeric tamarind herbal drink, traditionally known as jamu kunyit asam, remains widely consumed in Indonesia for its health benefits, including reducing menstrual pain, relieving inflammation, and refreshing the body. This study aimed to explore the utilization of turmeric (Curcuma longa) and tamarind (Tamarindus indica) as traditional herbal medicine in Sentul Village, Serang Regency. Using a qualitative descriptive approach, data were collected through interviews, observations, and documentation with local jamu producers. The findings revealed that the preparation of jamu kunyit asam is carried out using simple methods and natural ingredients without chemical additives. The main ingredients used are turmeric rhizome and tamarind pulp, which are known to contain curcumin, essential oils, flavonoids, and antioxidants with pharmacological properties. The herbal drink is primarily consumed by women for health maintenance and is stored in refrigerators to maintain its freshness for 2–3 days. Additionally, this traditional practice supports local livelihoods and preserves cultural heritage. However, consumption is not recommended for individuals with gastric ulcers due to the acidic nature of tamarind. This study highlights the potential of jamu kunyit asam as a culturally rooted and sustainable herbal remedy that can be further developed into a community-based local health product.